PEMBERDAYAAN LANSIA DALAM PENANGANAN HIPERTENSI MELALUI EDUKASI TERAPI KOMPLEMENTER AROMATERAPI LAVENDER - Mahdalena, Mahdalena; Hutagaol, Rutmauli; Suroto, Suroto (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Universitas Pattimura, 2025)
Hypertension is one of the health problems experienced by many elderly and requires a holistic and sustainable management approach. One complementary therapy that can help overcome stress and lower blood pressure is lavender aromatherapy (Lavandula angustifolia). The purpose of this community service activity is to increase the knowledge of the elderly about hypertension and the use of lavender aromatherapy as a complementary therapy. This activity was carried out on May 16-17, 2025, at the Matahari Posyandu, Guntung Paikat Village, Banjarbaru City, with a participatory education method involving the elderly as active participants, totaling 22. Education is delivered through visual media, simple language, and interactive discussions to ensure optimal comprehension. The results showed a significant increase in the elderly's knowledge about the benefits, how to use, and the safety of lavender essential oil. In addition, their understanding of the integration between medical medicine and complementary therapy has also improved. This community service activity proves that the right educational approach can empower the elderly to manage hypertension independently and improve their quality of life.